Efektivitas Edukasi Kesehatan Mata Berbasis Game dalam Meningkatkan Pengetahuan Siswa SD Negeri 01 Sampangan - Salma Rif’atun Nisa; Devinna Putri Mariyanda; Depi Eni Hutauruk; Kharisma Arda Nur Annisa Oktavianingtyas; Fifi Amalia; Kirana Jeany Aldyana; Syaika Yunia Mustafida (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Visual impairment among elementary school children remains a growing public health concern associated with excessive gadget use, prolonged near-work activities, and limited awareness of eye health behaviors. This study aimed to analyze the effectiveness of game-based eye health education in improving students’ knowledge regarding eye health and prevention of visual impairment at SD Negeri 01 Sampangan. The study employed a pre-experimental one-group pre-test and post-test design involving 24 students selected through total sampling. The intervention used educational games, including right-left games, picture guessing, eye health monopoly, and word-search activities. Data were collected using structured questionnaires and analyzed using paired samples test. The findings showed a significant increase in students with good knowledge from 25.0% to 50.0%, while poor knowledge decreased from 45.8% to 12.5%. Statistical analysis indicated a significant difference between pre-test and post-test scores (p < 0.001). Snellen chart examination also supported early detection of visual impairment among students. Game-based eye health education was effective as an interactive and preventive school health promotion strategy.